2020
DOI: 10.1029/2019gl085580
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Intense Cyclone on Short‐Term Sea Ice Loss in a Fully Coupled Atmosphere‐Ocean‐Ice Model

Abstract: Arctic cyclones may be associated with periods of locally enhanced sea ice loss during the summer, and some studies have found that an intense cyclone in August 2012 resulted in a rapid sea ice retreat. This study uses a coupled atmosphere‐ocean‐ice model (Navy‐ESPC) to explore the relationship between the 2012 cyclone and short‐term sea ice melting. There are two mechanisms of cyclone‐induced melting in Navy‐ESPC: turbulent mixing of a warm layer located at 15‐ to 35‐m depth increases bottom melting and warm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
(60 reference statements)
4
15
0
Order By: Relevance
“…However, cyclones are likely having a larger effect on sea ice cover as young and thin sea ice becomes more widespread in the Arctic (Rampal et al, 2009;Maslanik et al, 2011;Spreen et al, 2011;Lindsay and Schweiger 2015;Itkin et al, 2017). Despite uncertainty in whether cyclones are a significant source of seasonal or interannual variability in pan-Arctic sea ice cover (Rae et al, 2017), numerous studies have demonstrated that cyclones are indeed a source of local and short term variability in sea ice cover and concentration (Zhang et al, 2013;Stern et al, 2020;Lukovich et al, 2021), and these shortterm changes in sea ice are critical for navigability within the Arctic region. This study examines how the surface winds and atmospheric energy flux from recent Arctic summer cyclones affects sea ice concentration on synoptic weather time scales of 1-10 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cyclones are likely having a larger effect on sea ice cover as young and thin sea ice becomes more widespread in the Arctic (Rampal et al, 2009;Maslanik et al, 2011;Spreen et al, 2011;Lindsay and Schweiger 2015;Itkin et al, 2017). Despite uncertainty in whether cyclones are a significant source of seasonal or interannual variability in pan-Arctic sea ice cover (Rae et al, 2017), numerous studies have demonstrated that cyclones are indeed a source of local and short term variability in sea ice cover and concentration (Zhang et al, 2013;Stern et al, 2020;Lukovich et al, 2021), and these shortterm changes in sea ice are critical for navigability within the Arctic region. This study examines how the surface winds and atmospheric energy flux from recent Arctic summer cyclones affects sea ice concentration on synoptic weather time scales of 1-10 days.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclonic surface winds enhance sea ice divergence, which locally reduces sea ice concentration in the vicinity of a cyclone (Maslanik and Barry 1989;Kriegsmann and Brümmer, 2014;Lukovich et al, 2021). In addition, strong surface winds later in the summer are increasingly capable of mixing relatively warm sub-surface sea water upward toward the surface, which causes substantial melting along the ocean-facing side of sea ice (Steele et al, 2010;Zhang et al, 2013;Stern et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Strong cyclonic surface winds cause sea ice divergence (Brümmer et al., 2008; Itkin et al., 2017; Vichi et al., 2019), generate swells that break up sea ice (Asplin et al., 2012; Holt & Martin, 2001; Kohout et al., 2014; Vichi et al., 2019), and induce melt along the bottom of the sea ice by mixing warm subsurface seawater upward (Arntsen et al., 2015; Smith et al., 2018; Stern et al., 2020; Zhang et al., 2013). In addition, cyclones can enhance melting along the upper surface of the sea ice by increasing the downward component of both the sensible heat flux (Stern et al., 2020) and the longwave radiative flux (Persson, 2012; Shupe & Intrieri, 2004). Cyclone‐induced sea ice loss in the Arctic is superimposed on the poleward retreat of the sea ice edge that occurs between May and September of each year.…”
Section: Introductionmentioning
confidence: 99%
“…This sea ice loss coincided with a spike in the surface kinetic energy integrated over the sea ice. Previous studies have attributed ice loss following the 2012 cyclone to enhanced surface melt from turbulent atmospheric heat fluxes (Stern et al., 2020) as well as basal melt from turbulent mixing of warm subsurface seawater (Stern et al., 2020; Zhang et al., 2013). However, given its exceptional intensity and longevity over regions of thin ice, the effect of the 2012 cyclone on sea ice extent may not be representative of how the large number of weaker Arctic cyclones affect sea ice during the melt season.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the projection skill of climate models used to simulate future seasonal and interannual changes in sea ice volume can limit the value of the resulting navigability assessment [19,20]. These works generally provide a projection of the Arctic shipping routes with average monthly SIT and have enlightened decisions on the long-term development of the Arctic shipping industry; however, they cannot capture the sea ice evolution such as ice blockages induced by synoptic-scale processes (e.g., cyclones and atmospheric advection) owing to their coarse temporal resolution [21,22]. There is no study yet that estimates the trans-Arctic navigability using all-year-round SIT data and ATAM at a daily frequency.…”
Section: Introductionmentioning
confidence: 99%